Narasi Sosial dan Representasi Budaya Minangkabau dalam Film Onde Mande!: Analisis Naratif dengan Pendekatan Fisher dan Todorov - Aulia Gusnita; Emeraldy Chatra; Ernita Arif (JKOMDIS : Jurnal Ilmu Komunikasi Dan Media Sosial, 2025)
The Indonesian film industry has experienced rapid development with the presence of various films that are not only entertaining, but also full of social values ​​and messages. The film Onde Mande! is one of the films that highlights the richness of Minangkabau culture while containing social values ​​in a light and entertaining narrative. This study aims to analyze the narrative structure and social values ​​in the film Onde Mande! using the narrative theory approach of Tzvetan Todorov and Walter Fisher. Todorov's theory is used to analyze the storyline into three stages, namely balance, disturbance, and equilibrium. Meanwhile, Fisher's theory emphasizes the importance of meaning, narrative rationality (coherence and fidelity), and moral truths believed by the audience. The results of this study indicate that the narrative structure of the film Onde Mande! follows the pattern of initial balance, disturbance, and new balance. The narrative is delivered coherently, emotionally touching, and has a moral message. This film also depicts the social values ​​of the Minangkabau people, such as mutual cooperation, responsibility, sincerity, deliberation, and devotion to family and culture. Thus, this film is not only entertainment, but also contributes to communication studies, especially in the narrative analysis of films based on Indonesian culture.